Transpersonal Psychology and Maulawiyyah Sufi Dance in an Effort "Taqarrub" to Allah Swt - Faiz Badridduja; Lanjar Mustikaningwang; Ahmad Fasya Alfayyadl; Subaidi (JOUSIP: Journal of Sufism and Psychotherapy, 2022)
This article tries to reveal and describe one of the many ways to get closer to Allah Swt., namely through a less common path; the art of dance. This way is considered unique because the combination of dance is accompanied by dhikr and beautiful things are heard in the ears of the salik when the ritual occurs, salik here is also a special dancer who has received a mandate from the mursyid. In addition, the "taqarrub" effort is collaborated with transpersonal psychology where the Sufi Maulawiyyah dance is considered a spiritual experience in order to gain His pleasure. The research method used in this article is to use the library research method or library research, whether it comes from books or scientific journals that have a relationship or relationship in the main discussion of this research, while the type or nature in writing this article is descriptive analysis with an analytical approach. theoretical normative. Based on the findings here, the results of the discussion are considered capable of accommodating the Sufis, especially those who are of the Maulawiyyah sect who came from Turkiye and then spread to various countries including Indonesia, besides that this also proves that in classical Islam they are able to adapt or integrate with the development of the times, especially the development of the art world so as to add and complete insight into intellectual property and social sciences.